(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we try to extend and obtain some more results inspired by P. Goswami and Aljouiee [9]. Here we are introducing a new subclass of biunivalent functions by using q-derivative operator, quasi-subordination and convolution analytic bi-univalent functions. Also we find both some initial and general coefficient bounds.